Model penataan desa kerajinan kayu di Junrejo Kota Batu - A. Tutut Subadyo (University of Merdeka Malang, 2003)
The development of handicraft industrial villages is a strategic effort that is beneficial for increasing production and has broad implications for rural social, economic and physical development. This effort is carried out through a regional spatial planning model as an effort to realize the idea of the